2018
DOI: 10.1186/s12889-017-4991-3
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the knowledge, attitudes and practices on Zika virus in New York City

Abstract: BackgroundOver 900 travel-associated Zika virus cases have been identified in New York City (NYC), New York. A survey was administered in NYC adapted from the Knowledge, Attitudes, and Practices (KAP) survey on Zika virus developed by the World Health Organization (WHO).MethodsA standardized, self-administered, anonymous questionnaire was administered to a convenience sample in Manhattan and the Bronx from June 30th, 2016 to October 21st, 2016. Responses were grouped into six domains based on the content and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
45
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 4 publications
14
45
3
2
Order By: Relevance
“…18 By contrast, the sample population of surveys conducted in areas close to the outbreak regions, such as New York City, NY, was considered knowledgeable. 17 In New York City, 85% of the survey respondents identified mosquitoes as a mode of transmission and 95% reported an association between ZIKAV and microcephaly. 17 Migrants to Jordan from areas with risk of ZIKAV could participate in the transmission and the spread of this disease † The correct answer for the questions is "NO.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…18 By contrast, the sample population of surveys conducted in areas close to the outbreak regions, such as New York City, NY, was considered knowledgeable. 17 In New York City, 85% of the survey respondents identified mosquitoes as a mode of transmission and 95% reported an association between ZIKAV and microcephaly. 17 Migrants to Jordan from areas with risk of ZIKAV could participate in the transmission and the spread of this disease † The correct answer for the questions is "NO.…”
Section: Discussionmentioning
confidence: 99%
“…In New York City, NY, Samuel et al 17 showed that pregnancy was significantly associated with the knowledge about ZIKAV transmission but not with the knowledge of its complications or ZIKAV guidelines. Whereas, we showed that pregnant women, despite being the high-risk group of ZIKAV infection, have poor level of knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations